Agmatine Attenuates Brain Edema and Apoptotic Cell Death after Traumatic Brain Injury - Kim, Jae Young (J Korean Med Sci, 2015)
Traumatic brain injury (TBI) is associated with poor neurological outcome, including necrosis and brain edema. In this study, we investigated whether agmatine treatment reduces edema and apoptotic cell death after TBI. TBI was produced by cold injury to the cerebral primary motor cortex of rats. Agmatine was administered 30 min after injury and once daily until the end of the experiment. Animals were sacrificed for analysis at 1, 2, or 7 days after the injury. Various neurological analyses were performed to investigate disruption of the blood-brain barrier (BBB) and neurological dysfunction after TBI. To examine the extent of brain edema after TBI, the expression of aquaporins (AQPs), phosphorylation of mitogen-activated protein kinases (MAPKs), and nuclear translocation of nuclear factor-κB (NF-κB) were investigated. Our findings demonstrated that agmatine treatment significantly reduces brain edema after TBI by suppressing the expression of AQP1, 4, and 9. In addition, agmatine treatment significantly reduced apoptotic cell death by suppressing the phosphorylation of MAPKs and by increasing the nuclear translocation of NF-κB after TBI. These results suggest that agmatine treatment may have therapeutic potential for brain edema and neural cell death in various central nervous system diseases. GRAPHICAL ABSTRACT: [Image: see text]